2016
DOI: 10.1103/physrevb.93.014417
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the magnetization and compensation temperature in rare-earth orthoferrites and orthochromates

Abstract: We consider orthoferrite and orthochromite perovskites with the formula RMO3, where R is a lanthanide and M is Fe or Cr. We identify an atomistic interaction that couples the magnetic moments of the R and M cations with the oxygen octahedral rotations characterizing these crystals. We show that this interaction results in an effective magnetic field acting on the R atoms, which in turn explains several intriguing features of these compounds, such as the existence (or absence) of a net magnetization associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 37 publications
4
44
0
Order By: Relevance
“…4(a,b)), these AFM domains should also possess opposite directions for the magnetization of the Fe ions (positive or negative along the c-axis), since, within the Fe sublattice, the direction of the G-type antiferromagnetic vector dictates the direction of the WFM via a Dzyaloshinskii-Moriya (DM) interaction11. Moreover, these antiferromagnetic domains should also naturally favor opposite directions for the magnetization of the Dy ions (negative or negative along the c-axis), since F Dy and F Fe likely energetically prefer to be antiparallel to each other via another DM interaction19. However, at T = 100 K and H = −10 Oe during the standard hysteresis loop, the resulting “history-dependent” WFM state has a negative, small, but non-zero total magnetization, which can be explained by the facts that (i) there is a competition between the magnetic field desiring to make all the weak magnetizations of the Fe and Dy ions (i.e., belonging to the different AFM domains) aligned along its direction, and the aforementioned DM interactions1119 that prefer to induce the WFM of the Fe ions and/or the WFM of the Dy ions to be aligned opposite to the applied magnetic field in some AFM domains; and (ii) the magnetic field wins more and more this competition as its strength grows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(a,b)), these AFM domains should also possess opposite directions for the magnetization of the Fe ions (positive or negative along the c-axis), since, within the Fe sublattice, the direction of the G-type antiferromagnetic vector dictates the direction of the WFM via a Dzyaloshinskii-Moriya (DM) interaction11. Moreover, these antiferromagnetic domains should also naturally favor opposite directions for the magnetization of the Dy ions (negative or negative along the c-axis), since F Dy and F Fe likely energetically prefer to be antiparallel to each other via another DM interaction19. However, at T = 100 K and H = −10 Oe during the standard hysteresis loop, the resulting “history-dependent” WFM state has a negative, small, but non-zero total magnetization, which can be explained by the facts that (i) there is a competition between the magnetic field desiring to make all the weak magnetizations of the Fe and Dy ions (i.e., belonging to the different AFM domains) aligned along its direction, and the aforementioned DM interactions1119 that prefer to induce the WFM of the Fe ions and/or the WFM of the Dy ions to be aligned opposite to the applied magnetic field in some AFM domains; and (ii) the magnetic field wins more and more this competition as its strength grows.…”
Section: Resultsmentioning
confidence: 99%
“…A specific interaction between Fe and Dy neighboring ions can also exist in the Γ 4 (G x , A y , F z ) state, and is of the utmost importance since it can result in a net magnetization of Dy 3+ ions being either parallel or antiparallel to the net Fe 3+ sublattice moment aligned along the c -axis1920. Previous magnetizing studies of the Γ 4 phase of DFO single crystals reported that the magnetizations of Dy and Fe sublattices are parallel to each other121.…”
mentioning
confidence: 99%
“…[11,12], and U = 0, 4 or 6 eV is also used for the R ions in cases that their 4f electrons are treated as valence electrons as in Ref. [8,13]. The number of valence electrons of Fe ions is eight (3d 6 4s 2 ) while it is six (2s 2 2p 4 ) for O ions.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the today muchstudied iridates, 17 where Ir is a relative large cation at the B site of the perovskite lattice, present tilted phases as well, and so do the orthoferrites [18][19][20] that have recently gained renewed attention because of their multiferroic and spin-dynamical properties. Moving beyond the oxides, there are plenty of materials families displaying tilted phases, as e.g.…”
Section: Introductionmentioning
confidence: 99%